Planning Advanced Treatment of Tap Water Consumption in Universitas Pertamina - Hafizha Hasnaningrum; Betanti Ridhosari; I Wayan Koko Suryawan (Jurnal Teknik Kimia dan Lingkungan, 2021)
The wastewater treatment plant (WWTP) in Universitas Pertamina’s area is operating very well. The existence of a green campus program with a wastewater recycling indicator has become one of the challenges. Improving the WWTP effluent quality by adding an advanced treatment unit. This study aims to design advanced processing units and estimate the effluent yields and required costs. This study was conducted by conducting a field survey, collecting water quality data, and literature study. With planning discharge (Qpeak) of 8.45 m3 /hour, the land area required for the addition of advanced treatment is 105.85 m2 . Advanced treatment consists of 1 unit of Equalization Tank, 2 units of slow sand filter, 1 unit of sand washer, 2 units of microfiltration membrane, 1 disinfection body, and 2 reservoir units. These units it is expected to make effluent quality meets the drinking water quality standards with a TSS value of 0 mg/L, Ammonia (NH3-N) 0.35 mg/L, Organic Substances (KmnO4) 0.513 mg/L, Total Dissolved Solids (TDS) 23 mg/L, and Total Coliform 0 Total/100 ml of sample. The total cost needed to build an advance treatment for tap water consumption is Rp 374,727,334.